Commensal and Pathogenic Biofilms Alter Toll-Like Receptor Signaling in Reconstructed Human Gingiva - Shang, Lin; Deng, Dongmei; Buskermolen, Jeroen Kees; Roffel, Sanne; Janus, Marleen Marga; Krom, Bastiaan Philip; Crielaard, Wim; Gibbs, Susan (Frontiers in Cellular and Infection Microbiology, 2019)
The balance between the host and microbe is pivotal for oral health. A dysbiotic oral microbiome and the subsequent host inflammatory response are causes for the most common dental problems, such as periodontitis and caries. Classically, toll-like receptors (TLRs) are known to play important roles in host-microbe interactions by recognizing pathogens and activating innate immunity. However, emerging evidence suggests that commensals may also exploit TLRs to induce tolerance to the benefit of the host, especially in oral mucosa which is heavily colonized by abundant microbes. How TLRs and downstream signaling events are affected by different oral microbial communities to regulate host responses is still unknown. To compare such human host-microbe interactions in vitro, we exposed a reconstructed human gingiva (RHG) to commensal or pathogenic (gingivitis, cariogenic) multi-species oral biofilms cultured from human saliva. These biofilms contain in vivo like phylogenic numbers and typical bacterial genera. After 24 h biofilm exposure, TLR protein and gene expression of 84 TLR pathway related genes were investigated. Commensal and pathogenic biofilms differentially regulated TLR protein expression. Commensal biofilm up-regulated the transcription of a large group of key genes, which are involved in TLR signaling, including TLR7, the MyD88-dependent pathway (CD14, MyD88, TIRAP, TRAF6, IRAKs), MyD88-independent pathway (TAB1, TBK1, IRF3), and their downstream signaling pathways (NF-κB and MAPK pathways). In comparison, gingivitis biofilm activated fewer genes (e.g., TLR4) and cariogenic biofilm suppressed CD14, IRAK4, and IRF3 transcription. Fluorescence in situ hybridization staining showed the rRNA of the topically applied and invaded bacteria, and histology showed that the biofilms had no obvious detrimental effect on RHG morphology. These results show an important role of TLR signaling pathways in regulating host-microbe interactions: when a sterile gingival tissue is exposed to commensals, a strong immune activation occurs which may prime the host against potential challenges in order to maintain oral host-microbe homeostasis. In contrast, pathogenic biofilms stimulate a weaker immune response which might facilitate immune evasion thus enabling pathogens to penetrate undetected into the tissues.